On the asymptotic extension dimension - Repovs, D.; Zarichnyi, М. (Український математичний журнал, 2010)
We introduce an asymptotic counterpart of the extension dimension defined by Dranishnikov. The main result establishes the relationship between the asymptotic extensional dimension of a proper metric space and the extension dimension of its Higson corona.